Pengaruh Sosialisasi Manajemen Bencana Terhadap Kesiapsiagaan Siswa SMPN 2 Delitua Menghadapi Banjir - Susilawati Susilawati; Rika Halimah; Izmi Raditya Putri; Dinda Mutiara (Pelantar Press, 2026)
Flooding is one of the most frequent disasters in Indonesia and has significant impacts on students’ safety and learning activities in schools. Therefore, improving students’ disaster preparedness is essential to reduce the risks of flood disasters. One effort that can be implemented is disaster management socialization in the school environment. This study aimed to determine the effect of disaster management socialization on the preparedness of students at SMP Negeri 2 Delitua in facing floods. This study employed a quantitative approach with a pre-experimental one group pretest–posttest design. The respondents consisted of 30 students selected using a total sampling technique. The research instrument was a flood preparedness questionnaire covering three aspects: knowledge, attitude, and action. Disaster management socialization was conducted through interactive lectures, educational video screenings, and flood evacuation simulations. Data were analyzed using the Paired Sample t-Test with a significance level of 0.05. The results showed an increase in students’ knowledge scores after the socialization; however, the increase was not statistically significant (p 0.05). In the attitude aspect, a significant change was observed after the socialization (p 0.05), indicating increased awareness of flood risks. Meanwhile, the action aspect showed a significant improvement (p 0.05), indicating that students were more capable of taking concrete actions in responding to flood situations. In conclusion, disaster management socialization influences students’ preparedness, particularly in the aspects of attitudes and actions